2000
DOI: 10.1136/thorax.55.8.662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the seasonal patterns of asthma identified in general practitioner episodes, hospital admissions, and deaths

Abstract: Background-Seasonal variations in asthma are widely recognised. This study was undertaken to investigate the relative diVerences in seasonal patterns by age as they impact on episodes of care in general practice, hospital admissions, and deaths. Methods-General practice episode data from the Weekly Returns Service of the Royal College of General Practitioners, hospital admissions for asthma in England, and deaths registered as due to asthma in England and Wales over the years 1990-7 were examined. Age specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 13 publications
8
71
0
1
Order By: Relevance
“…Apart from their weather sensitivity (McGregor 2001), a characteristic of these diseases is the strong seasonality displayed. For example, strong winter peaks of asthma can be identified in general practitioner episodes, hospital admissions and deaths in England, Malta and areas covered by the European Community Respiratory Health Survey (Fleming et al 2000, Verlato et al 2000, Grech et al 2002. Eccles (2002) and Law et al (2002) have further noted that acute upper and lower respiratory tract viral infections also display clear winter peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their weather sensitivity (McGregor 2001), a characteristic of these diseases is the strong seasonality displayed. For example, strong winter peaks of asthma can be identified in general practitioner episodes, hospital admissions and deaths in England, Malta and areas covered by the European Community Respiratory Health Survey (Fleming et al 2000, Verlato et al 2000, Grech et al 2002. Eccles (2002) and Law et al (2002) have further noted that acute upper and lower respiratory tract viral infections also display clear winter peaks.…”
Section: Introductionmentioning
confidence: 99%
“…The CUE intervention had a positive effect on asthma health outcomes and a protective effect during periods of seasonal vulnerability, especially winter and spring. It has been previously reported that adverse asthma outcomes in middle age and elderly patient cohorts reach peak levels in the winter season, 17 driven largely by viral exacerbations. Similarly, the control group in this study, with a mean age of 50 years, experienced a marked increase in periods of worsening symptoms, oral steroid use, and urgent care use in the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…16 Figure 1 also compares the predicted estimate with the actual counts using the full model. The close approximation of the actually and predicted value demonstrates that the model provides an accurate fit of the time series data.…”
Section: Resultsmentioning
confidence: 99%